Comparative effectiveness of interventions for treatment of overweight and obesity: Review of latest studies - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
Overweight and obesity are amongst most common problems of our time and have a significant negative impact on somatic health. Recently have been published several systematic reviews and meta-analysis that evaluated the effectiveness of various methods for overweight and obesity treatment. These studies are not yet included in the clinical guidelines, but might contain important results.